Language Learning Difficulties of Students With Dyslexia: A Case Study at a Primary School - Vizhi, PA Kayal; Rathnasabapathy, Maya (Theory and practice in language studies, 2023)
Dyslexic learners have trouble learning English as a foreign language because of their difficulties in reading, focus, and sensory motor skills. Dyslexia is a specific learning disability derived from neurological deficits. This research aims at investigating the Language Learning Difficulties of learners with Dyslexia: A Case Study at a Primary School, Chennai District. This study is a descriptive research design. The subjects of the research are 19 teachers of dyslexic students at primary school, Chennai, District. The data were collected using a questionnaire and it was analyzed through the descriptive statistics technique. The result of the data analysis shows that students with dyslexia have challenges with reading, spelling, identifying sounds and letters, and decoding and recognizing words (vocabularies). In addition, the finding explored that teachers implement learners-center teaching methods and collaboratively work to enhance their students’ reading skills. Furthermore, the result showed that the use of assistive technology, multi-sensory instruction, and individualized support are effective interventions for enhancing the reading ability of dyslexic students. This study helps future researchers as a benchmark for further exploration.